Homie eaudiobook Poems. - Smith, Danez (HighBridge Audio, 2020)
Danez Smith is our president Homie is Danez Smith's magnificent anthem about the saving grace of friendship. Rooted in the loss of one of Smith's close friends, this book comes out of the search for joy and intimacy within a nation where both can seem scarce and getting scarcer. In poems of rare power and generosity, Smith acknowledges that in a country overrun by violence, xenophobia, and disparity, and in a body defined by race, queerness, and diagnosis, it can be hard to survive, even harder to remember reasons for living. But then the phone lights up, or a shout comes up to the window, and family-blood and chosen-arrives with just the right food and some redemption. Part friendship diary, part bright elegy, part war cry, Homie is the exuberant new book written for Danez and for Danez's friends and for you and for yours.